The Challenges of Anticorruption Education in Universities - Hapsari, Aprina Nugrahesthy Sulistya; Chariri, Anis (Asia Pacific Fraud Journal, 2024)
This study aims to describe about anti-corruption education in the learning curriculum of 2 undergraduate accounting study programs that are accredited A or Excellent at 2 universities in Central Java. This study uses descriptive analysis by taking research data from the official university website. The results of the study show that the two study programs consider anti-corruption education to be important in teaching students and needs to be integrated into the curriculum through compulsory courses, general activities such as seminars, and training to strengthen student soft skills. On the website, several matters related to anti-corruption education have been published, such as the vision and mission, curriculum, and news about general anti-corruption activities. The challenge going forward in the implementation of anti-corruption education lies in the integration of anti-corruption values into students, the specifications of courses that discuss anti-corruption education, and moral education in facing the 4.0 industrial revolution era to produce graduates with high integrity.